2014
DOI: 10.1021/ic502724n
|View full text |Cite
|
Sign up to set email alerts
|

Rich Structural Chemistry in New Alkali Metal Yttrium Tellurites: Three-Dimensional Frameworks of NaYTe4O10, KY(TeO3)2, RbY(TeO3)2, and a Novel Variant of Hexagonal Tungsten Bronze, CsYTe3O8

Abstract: Pure polycrystalline phases and single crystals of four new quaternary alkali metal yttrium tellurites, NaYTe4O10, KY(TeO3)2, RbY(TeO3)2, and CsYTe3O8, have been prepared by solid-state and hydrothermal reactions using A2CO3 (A = Na, K, Rb, and Cs), Y(NO3)3·6H2O, Y2O3, and TeO2 as starting reagents. X-ray diffraction analyses suggest that NaYTe4O10 exhibits a highly symmetric three-dimensional (3D) framework consisting of YO8 square antiprisms and chains of TeO4 polyhedra. Within the framework, six- (6-) and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 49 publications
4
12
0
Order By: Relevance
“…Thus, the Cs + cation should reside in the interlayer space and generate a layered structure of CsIn­(SeO 3 ) 2 (Figure c). Similar cation size effects on framework structures have been observed in various stoichiometrically equivalent alkali metal selenites and tellurites. …”
Section: Effect Of Cation Size On the Centricity And The Framework St...supporting
confidence: 59%
“…Thus, the Cs + cation should reside in the interlayer space and generate a layered structure of CsIn­(SeO 3 ) 2 (Figure c). Similar cation size effects on framework structures have been observed in various stoichiometrically equivalent alkali metal selenites and tellurites. …”
Section: Effect Of Cation Size On the Centricity And The Framework St...supporting
confidence: 59%
“…The contributions of other species between ML complexes, such as counterions and solutes, have been practically overlooked owing to their relatively little influence on the local coordination of molecular ions and thermodynamics that drives the reactions . Counterions have been generally used as charge-balancing species to control the ionic strength, metal-complex solubility, and overall packing of molecular ions. Nevertheless, our recent study demonstrates the correlation between the hydration enthalpies of countercations (A + = Li + , Na + , K + , Rb + , Cs + , NH 4 + , or NR 4 + ) and the formation of thorium nitrato molecular complexes from aqueous solution, wherein a transition from the more hydrated [Th­(NO 3 ) 5 ­(H 2 O) 2 ] − to less hydrated [Th­(NO 3 ) 6 ] 2– ML complex occurs with decreasing hydration enthalpies of counterions . Moreover, the electrochemical properties and chemical reactivity within a series of alkali-metal cerium­(III) 1,1′-binolate complexes can be fine-tuned by the choice of alkali metals .…”
Section: Introductionmentioning
confidence: 91%
“…Tellurites however, possess a rich and varied crystal chemistry because of the unpredictable and irregular coordination geometries adopted by the Te IV atoms, which can bond to between three and six O atoms. This behavior is characteristic of p-block cations with ns 2 np 0 electronic configurations and may be ascribed to a second-order Jahn−Teller (SOJT) effect, [6][7][8] which results in a stereochemically-active lone pair of electrons, 9,10 which must be spatially accommodated within the crystal structure. In previous studies, it has been found that the Te lone pairs can form one-dimensional lone-pair channels, 11 where TeOx (x = 3, 4, 5) polyhedra are connected to MOy units (M = metal cation) or two-dimensional lone-pair sheets, 12 whose interlayer spacing are large enough to accommodate other chemical species such as alkalimetal cations.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal cations prefer to bond with both oxygen and halide anions, while lone-pair cations prefer exclusively to coordinate to oxide anions. 10 This suggests that the crystal chemistry in transition metal halo-tellurite systems is governed not only by the asymmetric coordination of Te 4+ cations but also by bonding preferences of the transition metal ions for oxide and halide anions to form M(O,X)n polyhedra.…”
Section: Introductionmentioning
confidence: 99%